Is esketamine-based opioid-free anesthesia more superior for postoperative analgesia in obstructive sleep apnea patients undergoing bariatric surgery? A study protocol - Guo, Yongle; Chen, Lina; Gao, Zhongquan; Zhang, Min; Liu, Mengjie; Gao, Xiaojun; Liu, Yang; Zhang, Xiaoning; Guo, Na; Sun, Yongtao; Wang, Yuelan (Frontiers in Medicine, 2022)
Introduction Opioid-free anesthesia (OFA) can certainly prevent nausea and vomiting after bariatric surgery (BS), but its postoperative analgesic effect is still controversial. Obstructive sleep apnea (OSA) is a prominent feature of morbid obesity in BS and accounts for a very high proportion, which significantly increases the difficulty of patients’ airway management. Those patients will be more representative and highlight the advantages of OFA. It is not clear whether esketamine can play a more prominent role in OFA for postoperative analgesia. Therefore, this study aims to explore the postoperative analgesic effect of esketamine-based OFA on BS patients with OSA. Methods and analysis This single-center, prospective, randomized, controlled, single-blind study is planned to recruit 48 participants to undergo BS from May 2022 to April 2023. Patients will be randomly assigned to the OFA group and opioid-based anesthesia (OBA) group in a ratio of 1:1. The primary outcome is the Numeric Rating Scale (NRS) at different times postoperatively. Secondary outcomes include analgesic intake, the incidence and severity of postoperative nausea and vomiting (PONV), Leiden Surgical Rating Scale (L-SRS), postoperative agitation and chills, PACU stay time, EuroQol five-dimensional questionnaire (EQ-5D), length of hospital stay, intraoperative awareness, and hemodynamically unstable treatments. Discussion The results of this study may explain the analgesic effect of esketamine-based OFA on patients undergoing BS combined with OSA, and provide evidence and insight for perioperative pain management. Ethics and dissemination This study is initiated by the Ethics Committee of The First Affiliated Hospital of Shandong First Medical University [YXLL-KY-2022(035)]. The trial results will be published in peer-reviewed journals and at conferences. Clinical trial registration [https://clinicaltrials.gov/ct2/show/NCT05386979], identifier [NCT 05386979].